2011
DOI: 10.1002/dc.21652
|View full text |Cite
|
Sign up to set email alerts
|

Crush intraoperatory analysis in craniopharyngioma

Abstract: Intraoperative smear cytology provides a rapid and reliable intraoperative diagnosis and guidance to the neurosurgeon during surgical resection and lesion targeting. It also helps the surgeon to monitor and modify the approach at surgery. The aim of this article was a clinicopathological and cytomorphological intraoperative crush smear correlation in craniopharyngioma. Thirty craniopharyngiomas were included in this study. Twenty-seven cases were adaCP and only three cases were papCP. This series included 16 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…did a study on craniopharyngiomas, reporting an accuracy rate of 83.33%. [ 71 ] Another study was conducted, testing the smear technique on just chordomas; the reported accuracy was 70%, which may be due to the small sample size ( n = 22) and insufficient sample tissue. The accuracy of brain smears increased in correlation with clinical details and radiological findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…did a study on craniopharyngiomas, reporting an accuracy rate of 83.33%. [ 71 ] Another study was conducted, testing the smear technique on just chordomas; the reported accuracy was 70%, which may be due to the small sample size ( n = 22) and insufficient sample tissue. The accuracy of brain smears increased in correlation with clinical details and radiological findings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it presents the combined overall score (Overall star rating). It is important to note that each (✩) represents one point [11] 80 Goel et al 2007 [17] 3057 India [59] 4172 Austria Khamechian et al 2012 [31] 139 [71] Another study was conducted, testing the smear technique on just chordomas; the reported accuracy was 70%, which may be due to the small sample size (n = 22) and insufficient sample tissue. e accuracy of brain smears increased in correlation with clinical details and radiological findings.…”
mentioning
confidence: 99%